High dose vitamin D may improve lower urinary tract symptoms in postmenopausal women. Issue 173 (October 2017) - Oberg, Johanna; Verelst, Margareta; Jorde, Rolf; Cashman, Kevin; Grimnes, Guri
Highlights: Vitamin D insufficiency is common, and might have extraskeletal consequences. Lower urinary tract symptoms (LUTS) are prevalent in postmenopausal women. LUTS have been inversely associated with vitamin D intake and status. In this RCT, women receiving high dose vitamin D reported improvement in LUTS. The results need confirmation in an RCT specifically designed for the purpose. Abstract: Lower urinary tract symptoms (LUTS) are common in postmenopausal women, and have been reported inversely associated with vitamin D intake and serum 25-hydroxyvitamin D (25(OH)D) levels. The aim of this study was to investigate if high dose vitamin D supplementation would affect LUTS in comparison to standard dose. In a randomized controlled study including 297 postmenopausal women with low bone mineral density, the participants were allocated to receive capsules of 20 000 IU of vitamin D3 twice a week (high dose group) or similar looking placebo (standard dose group). In addition, all the participants received 1 g of calcium and 800 IU of vitamin D daily. A validated questionnaire regarding LUTS was filled in at baseline and after 12 months. At baseline, 76 women in the high dose group and 82 in the standard dose group reported any LUTS. Levels of serum 25(OH)D increased significantly more in the high dose group (from 64.7 to 164.1 nmol/l compared to from 64.1 to 81.8 nmol/l, p < 0.01). No differences between the groups were seen regarding change in LUTS except for a statistically significant reduction in the reported severity of urine incontinence in the high dose group as compared to the standard dose group after one year ( p <  0.05). The results need confirmation in a study specifically designed for this purpose.